2018
DOI: 10.1093/carcin/bgy109
|View full text |Cite
|
Sign up to set email alerts
|

The chemopreventive effect of withaferin A on spontaneous and inflammation-associated colon carcinogenesis models

Abstract: Chemopreventive effects and associated mechanisms of Withaferin A (WA) against intestinal and colon carcinogenesis remain unknown. We investigated the chemopreventive effect of WA on transgenic mouse APCMin/+ and chemically induced azoxymethane/dextran sodium sulfate (AOM/DSS) models of intestinal and colon carcinogenesis. Oral WA administration (4 mg/kg and 3mg/kg) inhibited tumor initiation and progression of intestinal polyp formation in APCMin/+ mice and colon carcinogenesis in the AOM/DSS mouse model. WA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…We have also demonstrated the chemopreventive effect of WA on spontaneous and inflammation-associated colon carcinogenesis models. WA inhibited the expression of inflammatory (interleukin-6, tumor necrosis factor-alpha, and cyclooxygenase-2) and pro-survival ( pAKT , Notch1, and nuclear factor kappa-light-chain-enhancer of activated B cells; NF-κB ) markers in APCMin/+ and AOM/DSS models [ 10 ]. In another study conducted in our lab, through use of a natural compound, Psoralidin inhibited Notch1-mediated EMT activation in Aldehyde dehydrogenase positive (ALDH+) and ALDH− breast cancer tumors [ 71 ].…”
Section: Natural Compounds Target Notch1 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also demonstrated the chemopreventive effect of WA on spontaneous and inflammation-associated colon carcinogenesis models. WA inhibited the expression of inflammatory (interleukin-6, tumor necrosis factor-alpha, and cyclooxygenase-2) and pro-survival ( pAKT , Notch1, and nuclear factor kappa-light-chain-enhancer of activated B cells; NF-κB ) markers in APCMin/+ and AOM/DSS models [ 10 ]. In another study conducted in our lab, through use of a natural compound, Psoralidin inhibited Notch1-mediated EMT activation in Aldehyde dehydrogenase positive (ALDH+) and ALDH− breast cancer tumors [ 71 ].…”
Section: Natural Compounds Target Notch1 Activationmentioning
confidence: 99%
“…Notch1 and its target gene, hairy-enhancer-of-split ( HES1 ), are expressed more in advanced colon tumors than in low-grade tumors [ 9 ]. Recently, we and others have shown that NOTCH1 signaling is key to CRC progression and should be exploited clinically, especially in patients already diagnosed with high-grade polyps or localized colon cancer [ 10 , 11 ]. Hence, this review focuses on the role of Notch1 in CRC and therapies that target different Notch1 signaling by inhibiting Notch1 activation in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Notch-1 signaling pathway plays a crucial role in the development of colon cancer and WFA has been shown to inhibit this signaling including Akt/NF-κB/Bcl-2 pro-survival pathways. A molecular link between Notch/Akt/mTOR signaling was established and WFA inhibition of Notch-mediated signaling aided in JNK-( c-Jun N-terminal kinase) mediated apoptosis in colon cancer cell lines, HCT-116, SW-480 and SW-620 [79,80].…”
Section: Role Of Ws and Wfa In Various Cancersmentioning
confidence: 99%
“…Cumulated, these findings conclude that WA determines the suppression of cell development and determines programmed cell death in CRC cells through mitochondrial dysfunction intermediated by ROS and JNK pathway; therefore, WA is considered to be a promising solution for the CRC therapeutic use. Chandrasekaran et al (2018) has shown that preventive chemo action on colon carcinogenesis patterns can be both spontaneous and associated with inflammation. This type of preventive chemo action of WA was evidenced on transgenic adenomatous polyposis coli (APCMin/+) mice, as well as on models of colon/ intestinal cancer chemically caused by dextran sodium sulphate/azoxymethane (DSS/AOM).…”
Section: Colorectal Cancermentioning
confidence: 99%